What drives China’s long-term economic growth trend? A re-measurement based on a time-varying mixed-frequency dynamic factor model - Liu, Dayu; Xu, Bin; Song, Yang; Wang, Qiaoru (Technological and Economic Development of Economy, 2023)
The unprecedented downward pressure of China’s economic growth trend raises several questions, including what the current level of China’s long-term economic growth trend is, and what drives and how to inhibit the downward trend. Therefore, we develop a time-varying mixedfrequency dynamic factor model using data with different start dates to measure the trend, and perform a real-time decomposition of changes in the trend. We find that the trend has entered a downward stage since 2007, left a high-speed phase since 2012, and stepped in an accelerated downward stage since 2018. The current level of the trend is about 4%. However, the lower limit of the 90% confidence interval is below 2%, which is lower than natural rate level. Additionally, decelerated capital deepening, diminishing demographic dividend and technological recession all drive the downward trend. Compared to the relatively weak push-down effects of capital deepening and demographic dividend that are less than two percentage points, the downward trend is mainly driven by technological recession. Given that technological progress is unlikely to improve significantly in the short run, mitigating the mismatch between technological progress and obsolete capital, revitalizing existing capital stock, and increasing the efficiency of technology utilization become more feasible means.